Role in cell physiology : a multi-volume treatise - Hesketh, John E.; Pryme, Ian F. (Cytoskeleton, 1995)
This volume deals with functions of the cytoskeleton in different cellular processes such as cell compartmentation and organelle transport, secretion and cell attachment.